The Development of Android Based Dictionary For Graphic Technique - Ika Agustina; Murtopo Murtopo (JURNAL ARBITRER, 2017)
Dictionary is one of the important media in learning English. Along with the rapid development of mobile technology at this time, the various applications for mobile is widely developed as a medium of learning, one of them is the application of Android-based dictionary. Dictionaries on mobile devices are more practical than conventional dictionaries, as users can receive information quickly anywhere without space and time constraints. Related to this, the research aims to create a dictionary application of English-Indonesian graphics techniques capable of running on android-based phones. This application is built to help and meet the needs of students majoring in graphic technique in searching for meaning and understand various English words related to science of graphics. The collection of words and phrases (word entries) related to the science of graphic technique is done through literature studies of books, internet and other relevant sources. In addition, the collection of words and phrases is also done by conducting in-depth interviews with lecturers or graphic technique experts. The programming languages used in making this language dictionary application use Java 2 Micro Edition (J2ME) and SQLite. The dictionary after being validated of 4.14 with good category) and tested received positive response from the students indicated with very positive questionnaire results.